2015
DOI: 10.1007/s10750-015-2419-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of benthic macroinvertebrates in a tropical reservoir cascade

Abstract: The functioning of systems arranged in cascades of reservoirs can be explained by the Cascading Reservoir Continuum Concept, providing a theoretical framework for addressing ecological processes. In this context, this study tested the following hypotheses: (i) the benthic macroinvertebrate assemblage shows a nested distribution along a reservoir cascade; and (ii) local factors explain the structure of the benthic assemblage in every reservoir along the cascade. Macroinvertebrates play essential role in aquatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
1
18
0
2
Order By: Relevance
“…The increasing number of dams in large rivers has changed the landscape, resulting in various effects on biodiversity, demanding new approaches to analyse these effects on ecosystem functioning and community structures (Santos et al., ). We observed that damming decreases zooplankton functional β‐diversity in river‐associated lakes.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of dams in large rivers has changed the landscape, resulting in various effects on biodiversity, demanding new approaches to analyse these effects on ecosystem functioning and community structures (Santos et al., ). We observed that damming decreases zooplankton functional β‐diversity in river‐associated lakes.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, new environmental conditions can act as environmental filters for the establishment of new species and the population dynamics of existing species, since the construction of dams can lead to the loss of biodiversity (Santos et al., ), and even the displacement of sensitive species to headwater regions (Oliveira et al., ). The ichthyofauna is recognized as one of the assemblies most impacted by habitat fragmentation caused by the construction of reservoirs (Agostinho et al., ; Barletta et al., ), mainly due to the sudden change of lotic to lentic environments.…”
Section: Introductionmentioning
confidence: 99%
“…there is no evolutionary history that allows these species to possess characteristics enabling them to live in artificial lakes. Thus, pre-adapted species will colonize and succeed in this new landscape and environment (Agostinho et al, 2016). To understand the population and colonization patterns of these species it is essential to provide knowledge on the basic population parameters, such as reproduction period, first maturation size, reproduction areas, growth rates, maximum length and mortality rate, which are often basic entry parameters in population and assessment models (Dei Tos et al, 2002;Zhang and Megrey, 2006;Maunder and Punt, 2013;Methot and Wetzel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These consequences can be observed in compartments along reservoirs and downstream it dams (Nogueira, 2000(Nogueira, , 2001Mitsuka & Henry, 2002). Among the several communities of aquatic ecosystems affected by a new lentic environment, the benthic macroinvertebrates show an important tool in recycling nutrients and in the change of energy and mass among trophic levels (Santos et al, 2015). The structure of insect community and other aquatic invertebrates can be modeled in relation to the natural and anthropic changes (Silveira, 2004).…”
Section: Introductionmentioning
confidence: 99%